(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
The linguistic risk-taking initiative for language teaching and learning was developed at the bilingual English-French University of Ottawa, Canada. The initiative encourages learners of either language to step out of their comfort zone and practice their language skills in authentic everyday contexts. The initiative originally included a passport-styled booklet where learners checked off linguistic risks that they had taken around campus to expand the scope of their language learning and to participate in real-life situations. Subsequently, a digital app was added to offer new features and affordances aimed at increasing engagement, confidence, and competence in the target language. This article showcases the digital app and presents preliminary results from a validation study of the tool. The initiative fits into a new general approach to language teaching and learning, grounded in insights from language socialization, plurilingualism, and positive psychology.